2005
DOI: 10.1103/physrevlett.95.108301
|View full text |Cite
|
Sign up to set email alerts
|

Internal Stress in a Model Elastoplastic Fluid

Abstract: Plastic materials can carry memory of past mechanical treatment in the form of internal stress. We introduce a natural definition of the vorticity of internal stress in a simple two-dimensional model of elastoplastic fluids, which generates the internal stress. We demonstrate how the internal stress is induced under external loading, and how the presence of the internal stress modifies the plastic behavior.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Models which take into account plastic deformation of elastic media under external fields can explain the memory effect of vibration. [26][27][28] Here, there is one big question about the other memory effect, namely the ''memory effect of flow'': some pastes remember the direction of vibration and flow, but others remember only the direction of vibration and cannot remember the flow direction. The emergence of the memory effect of flow depends on what kind of colloidal particles we use.…”
Section: Introductionmentioning
confidence: 99%
“…Models which take into account plastic deformation of elastic media under external fields can explain the memory effect of vibration. [26][27][28] Here, there is one big question about the other memory effect, namely the ''memory effect of flow'': some pastes remember the direction of vibration and flow, but others remember only the direction of vibration and cannot remember the flow direction. The emergence of the memory effect of flow depends on what kind of colloidal particles we use.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of rheology, some Maxwelltype constitutive equations admit a rheological analogue of vorticity that becomes frozen in the limit of slow stress relaxation. 15) Such a frozen field can be explicitly constructed in some elastoplastic fluid models, 16,17) which gives a possible clarification of the memory effect in pastes found by Nakahara and Matsuo 18) in experimental studies of desiccation cracks. They found that, shaking a layer of wet paste for several tens of seconds and then leaving it still until it dries (typically for a few days), one can produce a strikingly anisotropic crack pattern.…”
Section: Introductionmentioning
confidence: 99%
“…This, or one of its variants, is often invoked in the analysis of bulk foams. However, as in the recent work of Takeshi and Sekimoto [15], we also include an elastic response, so that the model we propose has four key ingredients: elasticity up to a yield stress, plasticity, internal viscosity, and a viscous drag force.…”
mentioning
confidence: 99%